Revolutionary Biology Education: Development of Advanced Biology Learning Through Websites and Learning Kits - Hendra Susanto; Ibrohim; Andi Basuki; Wiedia Carullina Purwanti; Ari Gunawan; Afis Baghiz Syafruddin (International Journal of Science and Society, 2023)
Biology education has become essential in developing students' scientific understanding and skills in facing global challenges. Advanced biology learning can be introduced to students as an effort to apply science in everyday life and innovative research. This field of biology has opportunities for promising career paths and jobs in science and technology. However, this learning has yet to be widely introduced regarding innovations in the field of biology in various aspects so that it can deepen students' understanding and competence in solving problems. This research aimed to develop websites and learning kits in advanced biology education. The method used was ASSURE, including analysis of student characteristics, setting performance targets, media development, material exploration, evaluation, and revision. The results obtained in the research, covering the validation analysis of biological material, had met the aspects of depth, feasibility, clarity, suitability for purpose, and use of language. Validation analysis of video-based learning media had fulfilled the aspects of video quality, audio clarity, content suitability, text readability, and context connectedness. The learning platform validation analysis had met user experience, content availability, and visual quality. Recommendations for further research include a validation process by experts and field implementation to determine the effectiveness of learning media.